The Role of Farm Household Saving for Oil Palm Replanting at Paser Regency, East Kalimantan - Mariyah, Mariyah; Syaukat, Yusman; Hartoyo, Sri; Fariyanti, Anna; Krisnamurthi, Bayu (International Journal of Economics and Financial Issues, 2018)
Oil palm replanting is a long-term investment decision and requires relatively large amount of capital. Decision of farm households for oil palm replanting was determined by their economic condition and behavior on production and consumption. The objectives of this research are to analyze the role of household saving behavior for oil palm replanting and to determine the factors affecting household saving for replanting purpose. The research conducted at Paser Regency, East Kalimantan Province. Data were collected from a survey to 113 households with the age of oil palm trees between 21and 33 years which are purposively sampled. The role of household saving for replanting was measured by economic ability of replanting, which is the ratio between replanting savings and the total requirement for replanting costs. The factors affected household saving for replanting was analyzed using a multiple regression method. The descriptive results of the study showed that 46.02 percent of the households'sampled had savings for replanting, while the rest 56.98 percent had no saving. Households' economic ability for replanting was only 10.81 percent, very far from the required costs. The factors that could household saving were land area to be replanted, total household income, and credit of household for non-replanting purpose; while the age of oil palm, household size, expenditure per capita and loan repayment variables could reduce the saving. The implication of this research are: households should plan and implement gradual replanting program; and they should increase the savings, particularly some years before achieving the optimal replanting age. Keywords: saving, farm household, oil palm, replanting. JEL Classifications: D10, D14, D24